2021
DOI: 10.3390/ijms22052428
|View full text |Cite
|
Sign up to set email alerts
|

The T Cell Repertoires from Nickel Sensitized Joint Implant Failure Patients

Abstract: Nickel (Ni2+) is one of the most common allergens, affecting around 10–15% of the general population. As the demand for orthopedic implant surgery rises, the number of surgical revisions due to joint implant failure also increases. There is evidence that some patients develop joint failure due to an immune response to a component of the implant, and we have found that Ni2+ is an especially important cause. Hence, understanding the mechanisms by which Ni2+ allergy induces joint implant failure becomes a critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…T cell mechanism of Ni-mediated hypersensitivity was studied in patients who have previously shown allergic reactions to Ni-containing CoCrMo. The result confirmed that a conserved glutamic acid in TCR CDR3β sequence provides a potential Ni binding site [ 122 ]. Although previous studies discussed the significant role of T cells in Ni-induced inflammation, a surprising study by Sato et al revealed that even nude mice (lacking mature T cells) have shown Ni allergy.…”
Section: Immune Response Differences Between Degradable and Non-degra...supporting
confidence: 63%
“…T cell mechanism of Ni-mediated hypersensitivity was studied in patients who have previously shown allergic reactions to Ni-containing CoCrMo. The result confirmed that a conserved glutamic acid in TCR CDR3β sequence provides a potential Ni binding site [ 122 ]. Although previous studies discussed the significant role of T cells in Ni-induced inflammation, a surprising study by Sato et al revealed that even nude mice (lacking mature T cells) have shown Ni allergy.…”
Section: Immune Response Differences Between Degradable and Non-degra...supporting
confidence: 63%
“…The increase of histidine‐containing CDR3 among metal‐specific TCR mirrored the histidine positions in the random repertoires, without indications for a preferred metal ion binding site. Apart from histidine, glutamic acid (E) has been discussed as a possible Ni 2+ ion binding site at the end of the CDR3β 56 . In our data, glutamic acid occurred frequently at position 4 (3′‐5′; 47% of random TCR; mean) but was not further increased among Ni 2+ ‐specific TCR (~42%; Figure S9).…”
Section: Resultsmentioning
confidence: 58%
“…Apart from histidine, glutamic acid (E) has been discussed as a possible Ni 2+ ion binding site at the end of the CDR3β. 56 In our data, glutamic acid occurred frequently at position 4 (3′-5′; 47% of random TCR; mean) but was not further increased among Ni 2+ -specific TCR (~42%; Figure S9).…”
Section: A Cdr3 Histidine Is Commonly Enriched Among Metal-specific Tcrmentioning
confidence: 45%
See 2 more Smart Citations